Analysis of Elastic Characteristics of Carbonate Reservoirs - M. A. Khazieva; A. B. Trapeznikova; M. A. Yarmoshkaeva (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2023)
The purpose of this study is to analyze the elastic characteristics of the carbonate reservoirs of the Bashkirian and Moscovian Stages of the middle section of the Carboniferous system of the oil field. As part of the study, acoustic and density curves were restored for the intervals where logging was not performed. The petrophysical interpretation of the data, the identification of reservoirs, and the assessment of reservoir properties were carried out. The elastic properties analysis of the rocks has been conducted, and the possibility of identifying reservoirs using elastic parameters has been assessed. Based on the results of the elastic characteristics analysis, it is possible to distinguish between reservoir and tight rocks on acoustic and shear impedance, as well as define a confident relationship between acoustic impedance and rock porosity